2010
DOI: 10.1089/ars.2009.2743
|View full text |Cite|
|
Sign up to set email alerts
|

Mammalian Mitochondrial Complex I: Biogenesis, Regulation, and Reactive Oxygen Species Generation

Abstract: Virtually every mammalian cell contains mitochondria. These double-membrane organelles continuously change shape and position and contain the complete metabolic machinery for the oxidative conversion of pyruvate, fatty acids, and amino acids into ATP. Mitochondria are crucially involved in cellular Ca 2+ and redox homeostasis and apoptosis induction. Maintenance of mitochondrial function and integrity requires an inside-negative potential difference across the mitochondrial inner membrane. This potential is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
319
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(328 citation statements)
references
References 300 publications
(419 reference statements)
4
319
0
5
Order By: Relevance
“…Fatty acids are targets for direct or indirect damage by ROS (1,(5)(6)(7)(8)16), particularly when ROS are produced by integral membrane enzymes in the respiratory chain or the photosynthetic apparatus (1,7,8,16,18). The R. sphaeroides σ E protein activates a transcriptional stress response to 1 O 2 , a ROS that is generated by integral membrane proteins of the photosynthetic apparatus (16,17,19).…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acids are targets for direct or indirect damage by ROS (1,(5)(6)(7)(8)16), particularly when ROS are produced by integral membrane enzymes in the respiratory chain or the photosynthetic apparatus (1,7,8,16,18). The R. sphaeroides σ E protein activates a transcriptional stress response to 1 O 2 , a ROS that is generated by integral membrane proteins of the photosynthetic apparatus (16,17,19).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of Complex I as a JNK-mediated event is an interesting observation, as tyrosine phosphorylation is thought to be the primary post-translational mechanism for controlling respiratory complex activity (44,45). Complex I is a 45-subunit protein complex that resides in the inner mitochondrial membrane with projections into the mitochondria inner/outer membrane space and the mitochondrial matrix (45).…”
Section: Discussionmentioning
confidence: 99%
“…S4C). Mitochondria are regarded as the major source of cellular ROS (18). Recent studies have reported that mROS promotes NLRP3 activation (19).…”
Section: Pai-2 Mediates Loss Of Mitochondrial Integrity and A Decreasmentioning
confidence: 99%